Upaya Masyarakat Di Desa Wisata Penglipuran Dalam Menjalankan Sapta Pesona - Lutfi Hendriyati (Journal of Tourism and Economic, 2020)
The village is a legal community unit that has territorial boundaries that are authorized to regulate and manage the interests of the local community based on local origins and customs that are recognized and respected in the system of Government of the Unitary State of the Republic of Indonesia (Undang undang Nomor 32 Tahun 2004). The purpose of this study is to explain and describe the Community Efforts in Penglipuran Tourism Village in implementing Sapta Pesona. The synergy between the community, government and other parties makes this Penglipuran village make this village the title of the cleanest village in the world. This predicate was given by TripAdvisor in 2016. This proves that the people in Penglipuran Tourism Village run Sapta Pesona well.